Eugenic Concerns, Population Policies and Puericulture in Interwar Greece - Theodorou, Vassiliki; Karakatsani, Despina (The Historical Review/La Revue Historique, 2021)
The scientific origins and the development of eugenic and racial theories formulated by physicians, jurists and intellectuals since the early twentieth century have only recently attracted scholarly attention. However, the dissemination of eugenic measures regarding the social policy that Greek interwar governments implemented to protect the health of mothers and children still remains an underresearched topic. Our contribution presents the main points of the discussion about the relation of eugenics and puericulture and traces its development among paediatricians in the 1920s and 1930s. It further looks into the stakes, the ambivalent attitude and the eugenic proposals of both liberal and authoritarian governments concerning the protection of childhood and motherhood as well as into their respective demographic policies during the interwar period.